The Global Sustainable Development Goals of the 2030 Agenda: The Case of the Iberarchivos Program - Santos, Luana Lobo dos; Pinto, Marli Dias de Souza (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
The Iberarchivos program, which is a financial fund for the implementation of archival projects, is a benchmark of archival cooperation in Ibero-America for archival development. Based on the perspectives of culture as a pillar of sustainable development advocated by the United Nations Educational, Scientific, and Cultural Organization (UNESCO) and the Quadruple Bottom Line (QBL), the aim of this study is to present the contributions of the Iberarchivos program to the achievement of the Sustainable Development Goals (SDGs). Methodologically, it is an applied, exploratory, and descriptive study in terms of objectives, as well as bibliographic and documentary research in primary sources as technical procedures. After a critical reading of each strategic plan for the Ibero-American partnership (PACCI) for the period of 2019 to 2026, all the initiatives related to the Iberarchivos program for the achievement of sustainable development will be identified and described to map the existence of sustainable practices and actions intended for the Ibero-American archives in their activities. This work has identified efforts and movements that highlight the relevance of guaranteeing the right of access to information, culture, and memory for citizenship and the objectives of the SDGs of the United Nations 2030 Agenda, as well as mobilization with other social sectors for the development and monitoring of cultural public policies. The conclusion of this research is that the contributions of the Iberarchivos program are essential for achieving the SDGs, consolidating the QBL, and, above all, the richness and diversity of Ibero-American culture in building sustainable knowledge for society in general and the archival community, as well as democratizing access to culture.